Lipopolysaccharide Lowers Cholesteryl Ester Transfer Protein by Activating F4/80+Clec4f+Vsig4+Ly6C− Kupffer Cell Subsets. Issue 6 (10th March 2018) - van der Tuin, Sam J. L.; Li, Zhuang; Berbée, Jimmy F. P.; Verkouter, Inge; Ringnalda, Linda E.; Neele, Annette E.; van Klinken, Jan B.; Rensen, Sander S.; Fu, Jingyuan; de Winther, Menno P. J.; Groen, Albert K.; Rensen, Patrick C. N.; et al.
Abstract : Background: Lipopolysaccharide (LPS) decreases hepatic CETP (cholesteryl ester transfer protein) expression albeit that the underlying mechanism is disputed. We recently showed that plasma CETP is mainly derived from Kupffer cells (KCs). In this study, we investigated the role of KC subsets in the mechanism by which LPS reduces CETP expression. Methods and Results: In CETP‐transgenic mice, LPS markedly decreased hepatic CETP expression and plasma CETP concentration without affecting hepatic macrophage number. This was paralleled by decreased expression of the resting KC markers C‐type lectin domain family 4, member f ( Clec4f ) and V‐set and immunoglobulin domain containing 4 ( Vsig4 ), while expression of the infiltrating monocyte marker lymphocyte antigen 6 complex locus C ( Ly6C ) was increased. Simultaneously, the ratio of plasma high‐density lipoprotein‐cholesterol over non–high‐density lipoprotein‐cholesterol transiently increased. After ablation hepatic macrophages via injection with liposomal clodronate, the reappearance of hepatic gene and protein expression of CETP coincided with Clec4f and Vsig4, but not Ly6C. Double‐immunofluorescence staining showed that CETP co‐localized with Clec4f + KCs and not Ly6C + monocytes. In humans, microarray gene‐expression analysis of liver biopsies revealed that hepatic expression and plasma level of CETP both correlated with hepatic VSIG4 expression. LPS administration decreased the plasma CETP concentration in humans. In vitro experiments showed that LPS reduced liver X receptor‐mediated CETP expression. Conclusions: Hepatic expression of CETP is exclusively confined to the resting KC subset (ie, F4/80 + Clec4f + Vsig4 + Ly6C − ). LPS activated resting KCs, leading to reduction of Clec4f and Vsig4 expression and reduction of hepatic CETP expression, consequently decreasing plasma CETP and raising high‐density lipoprotein (HDL)‐cholesterol. This sequence of events is consistent with the anti‐inflammatory role of HDL in the response to LPS and may be relevant as a defense mechanism against bacterial infections.